0146 Sevoflurane preconditioning promotes sleep reintegration from lipopolysaccharide induced shattered sleep. (25th May 2022) - Nemoto, Tsuyoshi; Irukayama-Tomobe, Yoko; Hirose, Yuki; Takahashi, Satoshi; Takahashi, Genki; Tanaka, Hiromu; Yanagisawa, Masashi; Kanbayashi, Takashi
Abstract: Introduction: Anesthesia and sleep partially share neural circuits, yet little is known regarding the effect of anesthetics on sleep. Anesthetic agents exhibit a variety of biological effects concomitant with anesthesia. Sevoflurane, one of the wildly used volatile anesthetics, is known to increase the survival of sepsis model mice. Systemic inflammation like sepsis increases the inflammatory mediators in the brain affecting sleep dynamics with increase in NREM and decrease in REM. We hypothesized that sevoflurane preconditioning positively impacts disturbed sleep caused by systemic inflammation. Methods: We conducted a prospective, randomized laboratory investigation in C57BL/6J mice. A mouse model of lipopolysaccharide (LPS)-induced systemic inflammation was employed to investigate the effects of sevoflurane on sleep recovery. We evaluated symptoms recovery through electroencephalography/electromyography (EEG/EMG) and histological studies. The mice were exposed to 2% sevoflurane before and after peritoneal injection of LPS. The EEG and EMG were recorded for 24 h after the procedure. Brain tissue was harvested after the sevoflurane/LPS procedure and was immunostained using individual antibodies against choline acetyltransferase (ChAT) and Fos.[YI1] We quantitatively analyzed the ChAT-positive and ChAT/Fos double-positive cells in the pedunculopontine tegmental nucleus and laterodorsal tegmental nucleus (PPTg/LDTg). Results: Compared to control mice, mice preconditioned with sevoflurane but not post-conditioned showed a significant recuperation in rapid eye movement (REM) sleep and waking time during EEG recording following the LPS challenge. They also demonstrated shorter REM latency and restored theta power, indicating an early recovery from LPS-altered sleep. The bouts of REM episodes were retained with sevoflurane preconditioning. The number of ChAT/Fos double-positive cells in the PPTg/LDTg decreased by LPS challenge. However, group with sevoflurane preconditioning followed by LPS challenge showed higher number of activated neurons, restoring physiological degree of activation. Conclusion: Compared to control mice, mice preconditioned with sevoflurane but not post-conditioned showed a significant recuperation in rapid eye movement (REM) sleep and waking time during EEG recording following the LPS challenge. They also demonstrated shorter REM latency and restored theta power, indicating an early recovery from LPS-altered sleep. The bouts of REM episodes were retained with sevoflurane preconditioning. The number of ChAT/Fos double-positive cells in the PPTg/LDTg decreased by LPS challenge. However, group with sevoflurane preconditioning followed by LPS challenge showed higher number of activated neurons, restoring physiological degree of activation. Support (If Any):